Thermomechanical Mean-Field Modeling and Experimental Characterization of Long Fiber-Reinforced Sheet Molding Compound Composites - Kehrer, Maria Loredana (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2019)
A discontinuous fiber-reinforced thermoset material produced by the Sheet Molding Compound process is investigated. Due to the process-related fiber orientation distribution, a composite with an anisotropic microstructure is created which crucially affects the mechanical properties. The central objectives are the modeling of the thermoelastic behavior of the composite accounting for the underlying microstructure, and the experimental characterization of the pure resin and the composite material.